Sociodemographic, lifestyle, and health factors associated with depression and generalized anxiety disorder among Malaysian adults - Cheah, Yong Kang; Omar, Mohd Azahadi; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (SAGE Publications Inc., 2020)
Objectives: Lowering the prevalence of mental health illness is one of the main public health concerns. The objective of the present study was to examine factors associated with depression and generalized anxiety disorder (GAD) among adults in Malaysia. Methods: Data were extracted from the National Health and Morbidity Survey 2011 (NHMS 2011), which is a nationally representative sample collected using a 2-stage stratified sampling method. A bivariate probit model was utilized to examine the influences of sociodemographic, lifestyle, and health factors on the likelihood of suffering from depression and GAD. Results: Age, gender, ethnicity, education, marital status, and self-rated health were significantly associated with depression and GAD. In particular, there were positive relationships between depression and GAD, and younger adults, females, Indian ethnic group, lower level of education, being unmarried, and self-rated poor health. Conclusions: Sociodemographic and health factors were associated with determining the risks of depression and GAD in Malaysia. With this information, future policies (eg, screening and treatment) could be targeted at those at most risk to develop depression and GAD.